Pengaruh Disiplin Kerja dan Motivasi Kerja Terhadap Kinerja Pegawai Pada Kantor Kecamatan Tigaraksa Kabupaten Tangerang - Novia Hoyirun Nisa; Feriadi; Wiwi Idawati (JURNAL EKONOMI, BISNIS DAN HUMANIORA, 2023)
All organizations are required to further improve employee performance in order to develop the organization. Many factors influence, one of which is Human Resources. Through self-discipline of each employee, it will increase employee performance. In addition to Discipline, Work Motivation is also a factor because Work Motivation is something that is within every employee that can influence whether there is an Influence of Work Discipline and Work Motivation on Employee Performance at the Tigaraksa District Office, Tangerang Regency.This research method uses quantitative methods. The sampling method uses a non-probability sampling method or saturated samples. The number of samples in this study were 53 respondents. Data collection techniques using questionnaires, interviews, observation and literature study. Then the test tool used is SPSS software. The results showed that there was a partial t influence of discipline and work motivation on employee performance. Work discipline with a value of 2,068 then work motivation 3,604 with a significantly less than 0.05. So it can be concluded that the discipline variable and the Work Motivation variable affect the Employee Performance variable. The results of this study simultaneously with the calculated f value of 59.670 greater than F calculated 3.18 so the variables of Discipline and Work Motivation have a joint effect on the Employee Performance variable. It can be concluded based on the results of the study that Discipline and Work Motivation on Employee Performance have a positive and significant relationship